Little Botany: A Mobile Game Utilizing Data Integration to Enhance Plant Science Education - Suphanut Jamonnak; En Cheng (International Journal of Computer Games Technology)
Mobile devices are rapidly becoming the new medium of educational and social life for young people, and hence mobile educational games have become an important mechanism for learning. To help school-aged children learn about the fascinating world of plants, we present a mobile educational game called Little Botany, where players can create their own virtual gardens in any location on earth. One unique feature of Little Botany is that the game is built upon real-world data by leveraging data integration mechanism. The gardens created in Little Botany are augmented with real-world location data and real-time weather data. More specifically, Little Botany is using real-time weather data for the garden location to simulate how the weather affects plants growth. Little Botany players can learn to select what crops to plant, maintain their own garden, watch crops to grow, tend the crops on a daily basis, and harvest them. With this game, users can also learn plant structure and three chemical reactions.